H2O2 as a better index of seed quality and mechanism of cucumber (Cucumis sativus) seed deterioration - AHMAD, DILSHAD; JAIN, S K; JOSHI, MONIKA A; ANAND, ANJALI; TOMAR, B S; KUMAR, SUNIL; HASAN, MUZAFFAR (The Indian Journal of Agricultural Sciences, 2021)
The present investigation was conducted at research farm of ICAR-Indian Agricultural Research Institute, New Delhi for 2016-17 and 2017-18 to study the seed deterioration in cucumber (Cucumis sativus L.) cv PusaBarkha by mimicking seed ageing with accelerated ageing. The fresh seeds were subjected to accelerated ageing at 40±1˚ C and 100% RH for a duration of 2, 4, 6 days along with control (0 days) in desiccators. With the progression of ageing, a gradual decline in the seed quality parameters, viz. seed germination and seed vigour indices was observed. The H2O2 content was within the threshold level from 0 to 4 days of ageing but beyond this, it damaged the cell membrane in seeds. Similarly, antioxidant activity (SOD, CAT, POX and higher GSH/GSSG ratio) increased initially and maintained the redox state by quenching the H2O2 effectively. Whereas, the content of H2O2 reached above the oxidative window as the activity of enzymes also decreased beyond 4 DAA. The study suggested that the H2O2 within oxidative window could be quenched efficiently; beyond this it is toxic and affects longevity as enzymes get inactivated with ageing in storage.